Monitoring and analysis MAGDAS data during ionospheric events / Norulhuda Mohmad - Mohmad, Norulhuda (2009)
Phenomena such as explosions on the sun create storms of radiation, fluctuating magnetic fields and swarms of energetic particles which travel through solar wind. At the moment they arrive at earth, they interact in complex ways with earth magnetic field. Some space weather storms can damage satellites, disable electric power grids and disrupt cell phone communication systems. This project focuses on monitoring and analysis Magnetic Data Acquisition System (MAGDAS) data during ionospheric events such as geomagnetic storms, Sudden Ionospheric disturbance (SID) and Travelling Ionospheric Disturbance (TID). The raw data is taken from MAGDAS unit at Ashibetsu Japan which supplied by Space Environment Research Center (SERC) Kyushu University, Japan. The data is then analyzed using MATLAB program. The variations of ionospheric events are based on Kp index from 13-17 April 2006.